Meningkatkan Perkembangan Keaksaraan Anak Melalui Pemanfatan Bahan Alam Bebatuan Pada Kelompok Bermain - Novarita, Agusten; Sari, Rika Partika; Haryono, Mimpira (UNIVED Press, Universitas Dehasen Bengkulu, 2022)
The purpose of this study was to find out whether using natural stone materials can improve children's literacy development in playgroups at HARAPAN PAUD, Dusun Baru Village, Ilir Talo District, Seluma Regency. Classroom Action Research (PTK) which is focused on classroom situations, or commonly known as classroom action research, the procedure used is in the form of a cycle. The main subjects in this study were 14 Kober children. This Classroom Action Research uses the John Elliot model where each cycle consists of four main activities, namely planning, implementing, observing, and reflecting which are carried out through two cycles, namely cycles I and II, each cycle consisting of one meeting. Data collection techniques using observation and documentation methods. Data analysis was carried out in a qualitative-quantitative descriptive manner with the emphasis being used to determine process improvements expressed in a predicate, while quantitative data analysis was used to determine yield improvements using percentages. The results of increasing children's literacy development through the use of natural stone materials in the beramin group at PAUD HARAPAN Seluma Regency in the first cycle of the first meeting was 69% and in the second cycle of the first meeting there was an increase of 83%. The conclusion of the study that through the use of natural stone materials can improve children's literacy development, it is proven that in cycle II there was a significant increase, the percentage of achievement was 83% with very good development criteria (BSB).